Class Frizzled GPCRs in GtoPdb v.2021.3. (2021) - Arthofer, Elisa; Dijksterhuis, Jacomijn; Hot, Belma; Kozielewicz, Paweł; Lauth, Matthias; Olofsson, Jessica; Petersen, Julian; Polonio, Tilman; Schulte, Gunnar; Strakova, Katerina; Valnohova, Jana; Wright, Shane
No abstract available